Applying the R2l Pedagogy To Improve Entrepreneurship Students’ Exposition Texts - Vencesla, Juan Gabriel Morales (Widya Mandala Catholic University Surabaya, 2021)
This article discusses a classroom action research (CAR) which applied Reading to Learn (R2L) to teach EFL reading and writing with Indonesian-speaking entrepreneurial management students at Universitas Katolik Widya Mandala Surabaya. R2L is a genre based literacy pedagogy based on Systemic Functional Linguistics. This CAR was designed based on an R2L pilot study conducted a few months earlier, and it consisted of three cycles, each one of which involved Detailed Reading, Joint Rewriting, and Joint Construction. The objective was to help the participants independently write an exposition text. Through observation and reflection, the class meetings of the second and third cycles were fine-tuned. Observation involved journal entries written by the teacher-researcher and the students. The effects of R2L on the exposition writing skills of the students were measured by comparing a pre-test and a post-test written by the participants. The criteria used to compare both texts were based on Rose and Martin (2012), and Martin and White (2005). It was found that the participants improved in terms of (1) Purpose; (2) Staging and Phases; and (3) Attitude. Thus, this study serves as further evidence of the effectiveness of the R2L Pedagogy to teach English writing in EFL contexts like Indonesia.